Dermal vasculature in psoriasis and psoriasiform dermatitis: A morphometric study - Shilpa Gupta; Mandeep Kaur; Ruchika Gupta; Sompal Singh; Leela Pant; P P Singh (Wolters Kluwer Medknow Publications, 2011)
Background: Vascular proliferation in the papillary dermis is considered to be an important and probably an early feature of psoriasis. Few morphometric studies have attempted to analyze the vascular changes. However, no study was found in the available literature comparing vascular changes between psoriasis and psoriasiform dermatitis. Materials and Methods : Skin biopsies from 25 cases each of psoriasis and psoriasiform lesions were immunohistochemically stained for CD34 (endothelial marker). Microvessel density (MVD), microvessel length density and ratio of microvessel area to papillary dermal area were calculated using image analysis software. Results: Skin biopsies from psoriasis showed higher staining for CD34 on light microscopy. Using morphometric techniques, microvessel length density was significantly higher in psoriasis compared to psoriasiform lesions (P value <0.05). MVD was also higher in psoriasis, though the difference was not significant. The ratio of microvessel area to dermal area was almost similar in both the groups. Conclusion : Our results indicate that vascular tortuousity and dilatation is significant only in psoriatic lesions. These results may assist in automated diagnosis of skin biopsies.